Academic freedom and the professional responsibilities of applied ethicists: a comment on Minerva - Dawson, Angus; Herington, Jonathan C. C. (My University, 2014)
Academic freedom is an important good, but it comes with several responsibilities. In this commentary we seek to do two things. First, we argue against Francesca Minerva's view of academic freedom as presented in her article ‘New threats to academic freedom’ on a number of grounds. We reject the nature of the absolutist moral claim to free speech for academics implicit in the article; we reject the elitist role for academics as truth-seekers explicit in her view; and we reject a possible more moderate re-construction of her view based on the harm/offence distinction. Second, we identify some of the responsibilities of applied ethicists, and illustrate how they recommend against allowing for anonymous publication of research. Such a proposal points to the wider perils of a public discourse which eschews the calm and careful discussion of ideas.
Keywords: Academic freedom; Applied ethics; Professional responsibility